2022
DOI: 10.18860/ua.v23i2.17489
|View full text |Cite
|
Sign up to set email alerts
|

SYAR’I AND ASTRONOMY INTEGRATION TO DETERMINE THE BEGINNING OF HIJRI CALENDAR: A Study of Elongation to Prove the Hilâl Testimony

Abstract: This article was motivated by the fact that most observers in Indonesia are inconsistent in determining the theoretical and practical beginning of the Hijri month. They only consider the aspect of the height of hilâl, but ignore the angle of elongation during the process of observing hilâl. This inconsistency occurs in the theory and practice reflected in the Decision of the Ministry of Religious Affairs of the Republic of Indonesia. Based on this case, the authors want to analyze the decision, especially the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Additionally, previous research by the author has found many accepted hilal testimonies documented in the decisions whose authenticity is questionable, accounting for 45.5% of all hilal confirmations from 1962-2021 (Nurkhanif et al, 2022). Nearly 90% of this 45.5% lack physical evidence of the hilal (Nurkhanif et al, 2022). However, the hypothesis from these research findings is limited to the reevaluation of astronomical hilal data and does not yet present physical data on the shape of the hilal.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, previous research by the author has found many accepted hilal testimonies documented in the decisions whose authenticity is questionable, accounting for 45.5% of all hilal confirmations from 1962-2021 (Nurkhanif et al, 2022). Nearly 90% of this 45.5% lack physical evidence of the hilal (Nurkhanif et al, 2022). However, the hypothesis from these research findings is limited to the reevaluation of astronomical hilal data and does not yet present physical data on the shape of the hilal.…”
Section: Introductionmentioning
confidence: 82%
“…Upon examination, it appears that there are indications of inconsistencies within the Ministry of Religious Affairs of Indonesia, as stated in the content of the decisions, particularly regarding the consistent application of the conditions under which the hilal can be seen, in accordance with the criteria of imkan al-rukyat that are still agreed upon and applied in Indonesia. Additionally, previous research by the author has found many accepted hilal testimonies documented in the decisions whose authenticity is questionable, accounting for 45.5% of all hilal confirmations from 1962-2021 (Nurkhanif et al, 2022). Nearly 90% of this 45.5% lack physical evidence of the hilal (Nurkhanif et al, 2022).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation